Changing the subject: the educational implications of developing emotional well-being - Ecclestone, Kathryn; Hayes, Dennis (Oxford review of education, 2009)
Claims that emotional well-being is synonymous with successful educational practices and outcomes resonate with contemporary political portrayal of well-being as integral to 'social justice'. In Britain, diverse concerns are creating an ad hoc array of therapeutic interventions to develop and assess attributes, dispositions and attitudes associated with emotional well-being, alongside growing calls to harness subject content and teaching activities as vehicles for a widening array of affective outcomes. There has been little public or academic debate about the educational implications of these developments for the aspirations of liberal humanist education. This article addresses this gap. Drawing on philosophical, political and sociological studies, it explores how preoccupation with emotional well-being attacks the 'subject' in two inter-related senses; the human subject and subject knowledge. It argues that it is essential to challenge claims and assumptions about well-being and the government-sponsored academic, professional and commercial industry which promotes them.